1999
DOI: 10.1017/s0007114599000409
|View full text |Cite
|
Sign up to set email alerts
|

Healthy dietary habits in relation to social determinants and lifestyle factors

Abstract: The aim of the present study was to evaluate the importance of social status and lifestyle for dietary habits, since these factors may influence life expectancy. We studied the association of four indicators for healthy dietary habits (fruits and vegetables, fibre, fat and Hegsted score) with sex, age, socio-economic status, education, physical leisure exercise, smoking and personal attention paid to keeping a healthy diet. Data were gathered with a self-administered quantitative food-frequency questionnaire d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
149
2
16

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(190 citation statements)
references
References 33 publications
(31 reference statements)
23
149
2
16
Order By: Relevance
“…Many surveys have found that people with higher education are more health conscious (Fraser et al, 2000;Greenwood et al, 2000;Johansson et al, 1999). This is consistent with what we found in the healthy group.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Many surveys have found that people with higher education are more health conscious (Fraser et al, 2000;Greenwood et al, 2000;Johansson et al, 1999). This is consistent with what we found in the healthy group.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies have found that higher education indicates a healthier lifestyle (Johansson et al, 1999;Fraser et al, 2000;Greenwood et al, 2000). However, in our study we found six different patterns representing different lifestyles.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Two studies demonstrated strong direct effects between portion sizes and energy intakes 38,39 . Seasonal variations in intakes were measured in countries differing considerably in their 25 Total fat USA Shelf space occupied by healthy foods in stores Objective De Castro (1992) 26 Energy, total fat USA Number of people present during meal Subjective De Craene (1990) 27 Total fat Belgium Location of residence, marital status Subjective (both) Diehr (1993) 28 Total 31 Energy, total fat USA Weekend/weekday, season Subjective Hellerstedt (1997) 32 Total fat USA Psychological demands, job latitude, job strain Subjective Johansson (1999) 33 Total fat Norway Location of residence, household income Objective (both) McCann (1990) 34 Energy, total fat, saturated fat USA Period of high/low workload Objective Morland (2002) 35 Total fat, saturated fat USA Whether or not there were the following food stores in the residential area:…”
Section: Resultsmentioning
confidence: 99%
“…Logistic regression analysis was used to further examine the associations between socio-economic circumstances and healthy food habits. As previous studies show that age (Johansson et al, 1999;Groth et al, 2001;Naska et al, 2006) and marital status (Roos et al, 1998;Naska et al, 2006) are associated with healthy food habits, and these two variables were adjusted for, as covariates in all models. We started by examining the covariate-adjusted associations between each socio-economic indicator and healthy food habits that is, each socio-economic indicator was first added to the model separately.…”
Section: Statistical Analysesmentioning
confidence: 99%